Eleições na Guiana: perspectivas para uma democracia étnica - Nahmias, Armando Carlos de Amorim (2016)
Despite its brief independent history, Guyana has experienced several periods of ethnic confrontation, almost reaching civil war. Given this scenario, the following research problem was formulated: what is the role of the ethnic voting for the electoral process in a plural society? To guide the work, a hypothesis was formulated that the electoral choices are strongly influenced by the ethnic alignment. This way, it was stablished that the purpose of the essay was to study the relevance of the ethnic issue in the Guyanese electoral system. The first objective was fulfilled throughout the third chapter, in which a historical panorama of the elections between 1947 and 2016 was constructed to show this country so marked by ethnic conflicts. In order to achieve the second, the forth chapter sought to smash various institutional aspects of that society. Finally, the third goal was performed during the fifth chapter, with the tabulation and comparison of all the data that were collected during the research. At the end of the project, this researcher could conclude that the ethnic vote has great importance in Guyanese society. The correlation between the 2012 census data and that of each region's vote in the 2011, 2015 and 2016 elections shows that apanjaht's policy, although not officially endorsed, has a strong appeal. A second conclusion reached during the research is that power-sharing institutes in Guyanese politics have not acted as efficient mechanisms to cushion the dissatisfactions of the ethnic groups surpassed in the elections.